Teknik Pengambilan Darah dan Pemisahan Serum Darah Sapi pada Sampel Untuk Uji Bovine Viral Diarrhea (BVD) - Visca, Annisa Septania; Azzahra, Intan Apriyola Ropi; Putra, Naufal Anugerah; Amanda, Norma Desti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Bovine Viral Diarrhea (BVD) is an infectious disease in cattle that can cause reproductive disorders, decreased productivity, and economic losses. The success of BVD examination is greatly influenced by the quality of blood serum used as a laboratory test material. This study aims to describe the blood collection technique and serum separation procedure for cattle and evaluate the quality of the resulting serum to support BVD laboratory examination. Sampling was conducted in July–August 2025 in seven districts in Bengkulu Province through the jugular vein, auricular vein, and coccygeal vein. Blood samples were collected using syringes or vacuum tubes without anticoagulant, then allowed to clot for 24 hours in an inclined position before the serum was separated and centrifuged at 3500 rpm for 10 minutes. The obtained serum was stored at −20°C until inactivated at 56°C for 30 minutes. The results showed that the serum collection and separation procedures produced clear serum, free from hemolysis, and suitable for use as a BVD laboratory test material. Thus, proper implementation of serum collection, separation, storage, and inactivation procedures plays an important role in ensuring sample quality and supporting the reliability of BVD examination